Dampak Bahasa Gaul terhadap Kemampuan Berbahasa Formal Remaja - Katharina Woli Namang; Trisnawati Bura; Yuni Frisanti Degu Bora (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
This research aims to analyze the impact of the use of slang on formal language skills among teenage students at the Muhammadiyah University of Maumere. Slang, as explained by Fogg (2018), is a form of language that develops within certain social groups, which is often more relaxed and not bound by formal linguistic rules. On the other hand, formal language skills are very necessary in academic and professional contexts. This research uses a quantitative approach with survey methods and interviews with randomly selected students. The research results show that although the majority of students are able to speak formal language in an academic context, there is a decrease in their ability to use formal language appropriately if they interact too often using slang. As explained by Supriyanto (2017), excessive use of slang can affect the mastery of formal language, especially in terms of grammar and word choice in accordance with formal communication norms. It is hoped that this research can provide a deeper understanding of the influence of slang on formal language skills and provide recommendations for increasing awareness of the importance of using formal language in official situations.